Gender differences and preferences in improved forage seeds demo farms experience amongst livestock farmers in Kenya and Uganda - Pazos Cardenas, Mateo; Junca Paredes, John Jairo; Sandoval, Danny; Waluse, Kenneth; Triana Ángel, Natalia; Burkart, Stefan; Jauregui, Rosa (2025)
This work analyses the gender differentiated preferences in improved forage seeds implemented in the Grass2Cash project, carried out in Kenya and Uganda by The Alliance of Bioversity International and CIAT. This project was a scaling initiative aimed at enhancing livestock productivity in East Africa by promoting the adoption of improved forages among smallholder farmers from 2021 to 2024, supporting forage businesses groups by providing high quality planting materials. The project collected data for more than 1.5000 smallholder farmers between both countries, disaggregated by different categories, such as gender, age, and caractheristics of householders, plots, forages planted, and incomes. The research’s originality lies in the effort to address the knowledge gap of gender analysis and women’s needs and preferences in the breeding developments, especially within the forages research field. Although some advances have been made in incorporating gender discussion in breeding for other types of crops, the forages are a step behind in this kind of efforts. The study finds that there is a similar proportion between men and women farmers in the Demo Plots, where majority of them are between 36 and 60 years and with a relatively high educational level (mostly with secondary completed, but also with college education). There are similarities between both men and women in terms of preferred type of forage planted, significant traits and majority of incomes related to milk sales (although much higher for men). In terms of benefits, there are also common aspects such as higher incomes and improvement of yield productivity; however, for women are also important time saving, family nutrition aspects and incomes for schooling (which don’t appear in men’s responses). These findings correlate with studies in other types of crops that demonstrate the benefits for including women in breeding processes but also are relevant and innovative data for the forages and breeding research field, that can open roads for deeper comparative analysis. Another important finding is that youth populations have significant differences in their uses of forages plots and incomes, which is field research that precises further development and attention.